(untitled) (Human Factors in Design, 2023)
In the education of the deaf, there are issues that need to be discussed, such as the need for interpreters in the classroom due to teachers’ lack of fluency in Libras, lack of teaching materials, as well as equipment, such as photography. Thus, the objective of this article is to present results of the doctoral research that aims to evaluate the self-learning of deaf people, using digital interfaces as materials and smartphone as photographic equipment. The methodology consisted of applying a mini photography course to 20 deaf subjects, sending a self-assessment questionnaire. The objective of the mini-course was to assess, with different age groups and demographics, the level of learning with the mini-course and the results of their self-assessments. The collected data demonstrated the corroboration of the hypothesis, there was autonomous learning.